Про деякі наслідки підписання Угоди про асоціацію з ЄС для металургії України - Нікіфорова, В.А. (Економіка промисловості, 2013)
Проаналізовано сучасний стан металургійної промисловості країн ЄС і розглянуто основні положення чинного у Євросоюзі «Action Plan for a competitive and sustainable steel industry in Europe». На основі цього визначено головні можливі проблеми та перспективи розвитку металургії України в коротко- та довгостроковій перспективі за умови підписання Угоди про асоціацію з ЄС з акцентом на екологічному й сировинному аспекті діяльності галузі.
Ключові слова: металургія, Європейський Союз, інтеграція, Угода про асоціацію України з ЄС. Проанализировано современное состояние металлургической промышленности ЕС и рассмотрены основные положения действующего в Евросоюзе «Action Plan for a competitive and sustainable steel industry in Europe». На основе этого определены главные проблемы и перспективы развития металлургии Украины в кратко- и долгосрочной перспективе при условии подписания Соглашения об ассоциации с ЕС с акцентом на экологическом и сырьевом аспекте деятельности отрасли.
Ключевые слова: металлургия, Европейский Союз, интеграция, Соглашение об ассоциации с ЕС. The current state of the steel industry in the EU is analyzed. It is revealed that to date, despite the presence of strong competitive advantages in industry, a number of negative trends has seen, which are expressed in the reduction of the volume of production, consumption, exports and imports of steel products, shortage of raw materials, reducing intra-regional marketingof metals, layoffs of workers.
Due to the worsening of main performance indicators of EU metallurgy a series of regulations is adopted by the European Commission aimed at solving the most pressing problems. The key documents concerning the general economic, social, resource and environmental issues are “Action Plan for a competitive and sustainable steel industry in Europe”, “Raw Material Initiative”, and “Directive of the European Parliament and of the Council on industrial emissions (integrated pollution prevention and control)”.
Based on the consideration of substantiveprovisions of these regulations in this article the problems and prospects of development of metallurgy in Ukraine in the short and long term outlook are given subject to signing the “Association Agreement between the European Union and its Member States, of the one part, and Ukraine, of the other part” with a focus on environmental and raw aspect of the industry. It is revealed that the main risks for the domestic steel industry may lie in the limitation ofsteel products sales, the need to implement a large number of European legal documents, and further consolidation of the role of the Ukrainian raw materials appendage. The main advantage of signing the Agreement for the Ukrainian steel industry consist in likely accelerating the modernization of metallurgical production as to meet European standards in product quality, energy efficiency, and environmental protection.
Keywords: metallurgy, the European Union, integration, the Association Agreementwith the EU.